LBP/BPI homologue in Eisenia andrei earthworms - Škanta, František; Procházková, Petra; Roubalová, Radka; Dvořák, Jiří; Bilej, Martin (Developmental and comparative immunology, 2016)
LBP/BPIs are pattern recognition receptors that are often present in vertebrates and in invertebrates, and they play a defense role against pathogens. We have identified 1698 bp cDNA sequence from the Eisenia andrei earthworm with predicted amino acid sequence that shares homology with the LBP/BPI family (EaLBP/BPI). Sequence analysis of EaLBP/BPI proved the existence of two conserved domains with the potential ability to bind LPS. The predicted molecular mass of the EaLBP/BPI protein is 53.5 kDa, and its high basicity (pI 9.8) is caused by its high arginine content. Constitutive transcription of the Ealbp/bpi gene was shown in all tested tissues, with the highest level in coelomocytes and seminal vesicles; the lowest level was detected in the intestine. On the contrary, another earthworm LPS-binding molecule CCF (coelomic cytolytic factor) was expressed only in the intestine and coelomocytes. In E. andrei coelomocytes, the transcription of Ealbp/bpi gene was up-regulated in response to bacterial stimulation, reaching a maximum at 8 and 16 h post stimulation with Bacillus subtilis and Escherichia coli, respectively.
Keywords: sekvence aminokyselin; Cloning, Molecular; krevní proteiny; Base Sequence; hybridizace in situ; kationické antimikrobiální peptidy; Oligochaeta; Reverse Transcriptase Polymerase Chain Reaction; In Situ Hybridization; klonování DNA; fylogeneze; Blood Proteins; polymerázová řetězová reakce s reverzní transkripcí; zvířata; Animals; molekulární sekvence - údaje; Molecular Sequence Data; Phylogeny; Amino Acid Sequence; Antimicrobial Cationic Peptides; sekvence nukleotidů